Differences in Corticoreticulospinal Tract Injuries According to Whiplash in Mild Traumatic Brain Injury Patients - Jang, Sung Ho; Yeo, Sang Seok; Kwon, Jung Won; Kwon, Young Hyeon (Frontiers in Neurology, 2019)
Background: This study investigated differences in postural control ability (PCA) and corticoreticulospinal tract (CRT) injury severity according to whiplash in patients with mild traumatic brain injury (mTBI). Methods: Thirty-one patients with mTBI and 21 healthy control subjects were recruited for this study. The balance error scoring system (BESS) was used for PCA assessment. Based on their history of whiplash, the patients were classified into two groups: group A – mTBI with whiplash injury and group B – mTBI without whiplash injury. Fractional anisotropy (FA), apparent diffusion coefficient (ADC), and tract volume (TV) values were estimated for the reconstructed CRTs in all subjects. Results: Significant differences were observed among the total BESS scores of patient groups A and B and the control group (p < 0.05); the patient group A BESS score was significantly higher than that of patient group B, and that of the patient group B was significantly higher than that of the control group. No significant differences were detected in the FA and ADC values of the CRTs of the two patient groups and the control group (p > 0.05). However, the TV values of the CRT showed significant differences; the TV of patient group A was significantly lower than that of patient group B and the control group, and that of patient group B was significantly lower than that of the control group (p < 0.05). Conclusions: We observed greater CRT injury severity and PCA impairment in mTBI patients with whiplash than in mTBI patients without whiplash. The results indicate that whiplash can increase the severity of axonal injury in mTBI patients.